Epidemiology of vaginal candidiasis among pregnant women attending Tikrit teaching hospital/Iraq. - Alsharifi, Ehan A. (Journal of the Faculty of Medicine Baghdad, 2018)
Back ground: Vaginal candidiasis is the second common infection among child bearing women. The disease is caused by yeast organism especially Candida albican. Pregnancy is one of the risk factors of the disease. It has been revealed that more than 75 % of women may experience an attach of the disease during their life time. Objectives: To study the epidemiological factors of vaginal candidiasis among pregnant women attending Tikrit teaching hospital out-patient clinic. Patients and methods: The study was conducted on a sample of (120) pregnant women. The demographic and epidemiologic information was obtained according to special designed questionnaire. The study was done over a period from 1/3/2017 to 16/4/2017. Vaginal swabs were taken from patients and sent to the lab for direct microscopically examination and cultured in special nutrient media. Results: About (29%) of study sample had vaginal candidiasis. There was a significant relation between a history of taking antibiotic, oral contraceptive drugs, diabetes mellitus and occurrence of the disease. The most frequent cases of vaginal candidiasis was from age group (25-35 years) (57.1%). Conclusions: About (29%) of pregnant women sample was affected by vaginal candidiasis. There was a significant relation between history of using oral contraceptive pills, broad spectrum antibiotics taking, diabetes mellitus and occurrence of the disease. المقدمة : داء المبيضات المهبلي هوثاني اشهر الامراض التي تصيب النساء الحوامل والذي يتسبب بواسطة الاصابة بنوع من الفطريات تسمى مبيضات البيكان . يعتبر الحمل احد العوامل التي تزيد احتمالية اصابة المرأة بهذا المرض حيث اوضحت الدراسات بان مايقارب 75٪ من النساء قد تعاني من المرض خلال فترة من فترات حياتهم . أهداف الدراسة:لدراسة العوامل الوبائية لداء المبيضات المهبلي بين النساء الحوامل الذين يراجعون المستشفى التعليمي في تكريت / العيادة الخارجية المرضى وطريقة عمل البحث :تم اجراء الدراسة على عينة مكونة من 120 من النساء الحوامل حيث تم جمع المعلومات الديموغرافية والوبائية لافراد العينة حسب استبيان خاص اعد لهذا الغرض . وقد اجريت الدراسة للفترة بين 1/3/2017 لغاية 16/4/2017 . لقد تم اخذ مسحات مهبلية من افراد العينة وارسلت للمختبر حيث تم فحصها مجهريا وكذلك تم زراعتها في اطباق خاصة تحتوي وسط غذائي خاص لذلك. النتائج:حوالي (29٪) من عينة الدراسة من النساء الحوامل كانت مصابة بداء المبيضات المهبلي وكما اظهرت الدراسة وجود علاقة كبيرة بين تناول المضادات الحيوية من قبل المرأة الحامل وتناول حبوب منع الحمل وزيادة الأصابة بالمرض وكما تبين وجود علاقة ايضا بين اصابة الحامل بداء السكري وزيادة حدوث المرض. وكانت الحالات الأكثر شيوعا لداء المبيضات المهبلي بين الفئة العمرية (25-35 سنة) (55.8٪) الاستنتاجات: حوالي (29٪) من عينة النساء الحوامل كانت مصابة بداء المبيضات المهبلي. وتبين وجود علاقة كبيرة بين استخدام حبوب منع الحمل، والمضادات الحيوية من قبل الحامل وكذلك اصابتها بداء السكري و زيادة حدوث المرض .